The Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd004294.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for older people in long-term care

Abstract: Provision of physical rehabilitation interventions to long-term care residents is worthwhile and safe, reducing disability with few adverse events.Most trials reported improvement in physical condition. However, there is insufficient evidence to make recommendations about the best intervention, improvement sustainability and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 92 publications
1
37
0
2
Order By: Relevance
“…However, they failed to show any effects on functional performance assessed as grip strength, walking ability, stair climbing and mobility. In contrast, in three systematic reviews [1,11,12] evidence was found showing that physical training had positive effects on mobility, physical functioning and cognition in institutionalized older patients. A Cochrane study [1] concluded that physical rehabilitation in long-term care residents is worthwhile and safe, that it reduces disability and leads to few adverse events such as pain, chest pain or loss of balance.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, they failed to show any effects on functional performance assessed as grip strength, walking ability, stair climbing and mobility. In contrast, in three systematic reviews [1,11,12] evidence was found showing that physical training had positive effects on mobility, physical functioning and cognition in institutionalized older patients. A Cochrane study [1] concluded that physical rehabilitation in long-term care residents is worthwhile and safe, that it reduces disability and leads to few adverse events such as pain, chest pain or loss of balance.…”
Section: Introductionmentioning
confidence: 96%
“…As a consequence of the increasing number of older people in the years to come, the demand for long-term residential care will increase [1]. When an older person has moved to a nursing home, a deterioration in health and an increasing dependence in activities of daily living (ADL), for example walking and dressing, is often seen [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Функциональный дефицит у пациентов пожилого и старческого возраста, степень его проявления и правильность диагностики во многом определяют объём и вид предо-ставляемой помощи [1,2]. Нужно сказать, что при традиционной системе симптомати-ческой диагностики по нозологиям данный медико-социальный гериатрический син-дром часто остаётся неучтённым, что суще-ственно влияет на эффективность курации пациентов данной возрастной группы [3,4].…”
Section: Evaluation Of the Syndrome Of Functional Deficit In Elderly unclassified